Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/lio2.23
|View full text |Cite
|
Sign up to set email alerts
|

The true malignancy rate in 135 patients with preoperative diagnosis of a lateral neck cyst

Abstract: ObjectiveIn this study, the true malignancy rate in 135 patients with a preoperative tentative diagnosis of a lateral neck cyst (LNC) was assessed. Furthermore, the sensitivity and specificity of fine needle aspiration of suspected LNC were evaluated and the diagnostic delay was analyzed.Study DesignThis study was retrospective in design and included all patients who had undergone surgery for a suspected LNC in four secondary hospitals in the eastern regions of Denmark during the period of 2009 to 2012.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
4
12
1
Order By: Relevance
“…Our incidence of 14% cancer in lateral neck cysts is in keeping with other such reports (6.9% -22%) [1,2,3] . This study was initiated in 2003-4 after two 'near misses' in such lateral cysts in whom the cancer was picked up by the senior author who had not long since joined the team in Northamptonshire.…”
Section: Discussionsupporting
confidence: 93%
“…Our incidence of 14% cancer in lateral neck cysts is in keeping with other such reports (6.9% -22%) [1,2,3] . This study was initiated in 2003-4 after two 'near misses' in such lateral cysts in whom the cancer was picked up by the senior author who had not long since joined the team in Northamptonshire.…”
Section: Discussionsupporting
confidence: 93%
“…Authors Riva et al reported a monocentric study with 190 pediatric patients with neck masses localized in all regions of the neck [ 15 ]. The three largest studies investigating LNM in adult population included data from 135 patients and were monocentric [ 16 , 17 ], and multicentric [ 18 ]. Therefore, this study presents the largest monocentric patient cohort to date, involving 250 children who underwent surgical treatment or sclerotherapy for a LNM.…”
Section: Discussionmentioning
confidence: 99%
“…The false-negative range of FNAB is 33% to 83% in the diagnosis of cervical cystic metastasis. [ 8 ] However, this may be attributed to sampling errors, and specimens can be obtained from the wall or solid part of the capsule to improve diagnostic accuracy. Moreover, the level of thyroglobulin (TG) can be measured to evaluate a metastatic cystic lesion of the thyroid.…”
Section: Discussionmentioning
confidence: 99%